Role of nanoparticles in elimination of biofilm produced by pathogenic bacteria - Samina Kousar; Atia Iqbal; Shafqat Rasool; Hafiz M. N. Iqbal (Journal of Contemporary Pharmacy, 2022)
Biofilm is a structured conglomeration of bacteria entrenched in a polymer matrix that is self-produced and contains DNA, polysaccharide, protein, and cause chronic infections. Pseudomonas aeruginosa lung infection is one of the well stated examples of pathogenic biofilms in cystic fibrosis patients. Due to mutating nature of the pathogens high antibiotic resistance will develop that make antibiotic treatment ineffective against repeated infections that are related to indwelling medical devices. Normally it was considered that nanoparticles are not larger than 100 nm, and their development to fight infection has gained popularity over the several decades. Different types of nanoparticles were introduced to treat biofilm infections in which silver nanoparticles were considered to be more efficient than all others. Maximum zone of inhibition in case of silver nanoparticles was found to be 40 mm against S.aureus, whereas maximum zone of inhibition with ZnO nanoparticles was 16 mm against Campylobacter jejuni, while in case of selenium nanoparticles and iron oxide nanoparticles zone of inhibition was time dependent and concentration dependent respectively. The order of antibacterial activity was like that Ag-Np>ZnO>CuO>Fe2O3. In this review article we discussed different biofilm producing pathogens that were isolated from different locations in latest research and to evaluate the role of nanoparticles in eradicating these pathogenic microbes.